2021
DOI: 10.1186/s12882-020-02219-4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial glycocalyx damage in kidney disease correlates with uraemic toxins and endothelial dysfunction

Abstract: Background Damage to the endothelial glycocalyx is an early indicator of vascular damage and a potential marker of endothelial dysfunction. This study aimed to assess the relationship between markers of glycocalyx damage, endothelial dysfunction, and uraemic toxins in patients with chronic kidney disease. Methods Healthy controls, CKD patients, dialysis patients, and kidney transplant recipients had biochemical markers of glycocalyx damage (syndeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 52 publications
6
40
0
Order By: Relevance
“…The glycocalyx of the endothelium is also damaged in CKD, which is evidenced by the excessive shedding of its components such as syndecan-1, hyaluronan and heparan sulfate. Clinical studies have demonstrated that syndecan-1 and hyaluronan levels are elevated in the serum of patients with advanced CKD and are correlated with PCS and IS serum levels (Vlahu et al, 2012;Padberg et al, 2014;Liew et al, 2021). An increase in syndecan-1 serum levels and a reduction in the thickness of the endothelial glycocalyx have been shown in an animal model of CKD (Padberg et al, 2014).…”
Section: Uremic Toxins In Endothelial Dysfunctionmentioning
confidence: 99%
“…The glycocalyx of the endothelium is also damaged in CKD, which is evidenced by the excessive shedding of its components such as syndecan-1, hyaluronan and heparan sulfate. Clinical studies have demonstrated that syndecan-1 and hyaluronan levels are elevated in the serum of patients with advanced CKD and are correlated with PCS and IS serum levels (Vlahu et al, 2012;Padberg et al, 2014;Liew et al, 2021). An increase in syndecan-1 serum levels and a reduction in the thickness of the endothelial glycocalyx have been shown in an animal model of CKD (Padberg et al, 2014).…”
Section: Uremic Toxins In Endothelial Dysfunctionmentioning
confidence: 99%
“…As a result, leukocytes in the blood circulation can adhere more easily to vascular endothelial cells. This process promotes the development of inflammation and endothelial dysfunction ( Mulivor and Lipowsky, 2004 ; Vestweber, 2015 ; Bui et al, 2020 ; Liew et al, 2021 ). Therefore, glycocalyx shedding is an important factor in vascular endothelial dysfunction.…”
Section: The Role Of the Endothelial Glycocalyx Layer In Inflammation And Endothelial Dysfunctionmentioning
confidence: 99%
“…They therefore suggested that estimation of endothelial glycocalyx dimension by SDF imaging might not be useful for cardiovascular risk prediction [16]. Along similar lines, a recent study was unable to detect a difference in the PBR level between healthy controls, persons with chronic kidney disease, persons on dialysis, and in kidney transplant recipients [14]. On the contrary, Mulders et al found that first degree relatives of persons with premature coronary artery disease were characterized by a higher PBR compared to healthy controls and concluded that sublingual capillary microvascular dysfunction might be useful for early risk prediction within families with premature coronary artery disease [17].…”
Section: Associations Between Endothelial Glycocalyx Dimensions and Cardio-renal Risk Factorsmentioning
confidence: 99%
“…Results have been inconsistent. Some studies could not demonstrate an association between glycocalyx size and cardiovascular or renal disease [14,15] and concluded that the technique might not contribute to cardiovascular risk stratification [16]. Whereas a higher PBR in first degree relatives of persons with premature coronary artery disease as compared to healthy controls has been described [17].…”
Section: Introductionmentioning
confidence: 99%